2019
DOI: 10.1080/21691401.2019.1669622
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: The anti-osteosarcoma property of ailanthone through regulation of miR-126/VEGF-A axis

Abstract: Background: Despite the characters of the resistance of tumour of ailanthone (AIL) were found in various tumour cells, its effect on osteosarcoma is still unclear. Herein, we attempted to see the effects of AIL on an osteosarcoma cell line MG63. Methods: MG63 cells were treated by AIL, following which CCK-8 assay, BrdU assay, Transwell assay and Western blot were utilized to detect cell proliferation, migration, invasion and apoptosis. miR-126 expression in osteosarcoma tissues and cell lines was measured by q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…A number of studies have demonstrated that abnormal expression of miRNA (miR-27a, 95-3p, 195 and 133b) was associated with osteosarcoma growth, metastasis and prognosis ( 77 79 ). For example, Kong et al ( 47 ) revealed that different concentrations of AIL inhibited MG63 osteosarcoma cell viability (P<0.01 or P<0.001) and proliferation (P<0.01) compared with those in the control group by increasing the levels of miR-126. Furthermore, cell migration and invasion were also inhibited by AIL, whereas the rate of apoptosis was increased.…”
Section: Ailanthone (Ail) As An Anti-tumor Drugmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have demonstrated that abnormal expression of miRNA (miR-27a, 95-3p, 195 and 133b) was associated with osteosarcoma growth, metastasis and prognosis ( 77 79 ). For example, Kong et al ( 47 ) revealed that different concentrations of AIL inhibited MG63 osteosarcoma cell viability (P<0.01 or P<0.001) and proliferation (P<0.01) compared with those in the control group by increasing the levels of miR-126. Furthermore, cell migration and invasion were also inhibited by AIL, whereas the rate of apoptosis was increased.…”
Section: Ailanthone (Ail) As An Anti-tumor Drugmentioning
confidence: 99%
“…Furthermore, cell migration and invasion were also inhibited by AIL, whereas the rate of apoptosis was increased. Protein expression levels of cyclin D1 and Bcl-2 were decreased, while Bax, cleaved PARP and cleaved caspase-3 were increased following treatment of MG63 cells with AIL compared with untreated cells ( 47 ). In addition, PTEN protein expression levels were increased; however, PI3K and AKT phosphorylation levels were decreased ( 47 ).…”
Section: Ailanthone (Ail) As An Anti-tumor Drugmentioning
confidence: 99%
“…Interestingly, five independent recent studies have underlined the capacity of AIT to regulate specific microRNA (miR), which are short (18–25 nucleotides), noncoding RNAs that posttranscriptionally control the expression of target genes. As illustrated in Figure 5, AIT downregulates the oncogenic miRNA miR‐21 (P. Yang et al, 2018) and upregulates the tumor suppressor miRNAs miR‐126 (Kong et al, 2019), miR‐195 (Hou et al, 2019), miR‐449a (Y. Zhang et al, 2019), and miR‐148a (Gao et al, 2019). These independent studies are briefly presented (Table 2).…”
Section: Regulation Of Mi‐rnas Expression and Functionmentioning
confidence: 99%
“…miR‐126 is viewed as a tumor suppressor, notably in digestive system cancers where it downregulates various oncogenes (Hu, Xiong, Chen, Zhu, & Zhou, 2019). AIT was found to upregulate miR‐126 in MG63 osteosarcoma cells and this effect was responsible for inhibition of cell growth, migration and invasion (Kong et al, 2019). The effects of AIT are similar to those observed upon transfection of miR‐126 in osteosarcoma cells, leading to inhibition of proliferation, migration, invasion, and epithelial to mesenchymal transition, through inactivation of JNK and JAK1/STAT3 pathways (Jiang, Zhang, Liu, Gu, & Wu, 2017).…”
Section: Regulation Of Mi‐rnas Expression and Functionmentioning
confidence: 99%
See 1 more Smart Citation